Gene flow from wheat (Triticum aestivum L.) to jointed goatgrass (Aegilops cylindrica Host.), as revealed by RAPD and microsatellite markers - Guadagnuolo, Roberto; Savova-Bianchi, D.; Felber, François (My University, 2001)
In order to estimate the potential of gene flow between wheat (Triticum æstivum L.) and jointed goatgrass (Aegilops cylindrica Host.), we carried out mixed pollinations in experimental and natural conditions. A set of species-specific RAPD (random amplified polymorphic DNA) and microsatellite markers were used to detect the presence of parental markers in the progeny of the plants used in these experiments. No hybrids were found within the offsprings of the plants used for the greenhouse experiments, while 85 Ae. cylindrica×T. æstivum hybrids were found within 2400 analyzed F1 plants resulting from the field pollinations. The hybridization rates for individuals of different populations of the wild species differed considerably: 1% for two populations known for more than 90 years versus 7% for a newly discovered population. Most of the hybrids were completely sterile, but five of them produced 13 seeds (BC1) by backcross with Ae. cylindrica. Twelve seeds germinated and generated viable and partly fertile plants. About 25% of the wheat specific RAPD markers were found in the BC1 plants, indicating that introgression of wheat DNA into Ae. cylindrica is possible. In addition, one microsatellite marker, known to be situated on the D genome (a genome shared by both species), was also found in the BC1 plants.
Keywords: gene flow; risk assessment; introgression; wheat; jointed goatgrass